2017
DOI: 10.1007/s13762-017-1342-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-matrix environmental monitoring to assess heavy element distribution around a municipal solid waste landfill in Italy

Abstract: Multi-matrix environmental monitoring was used to evaluate the influence of a municipal solid waste landfill (Ginestreto, Emilia Romagna, Italy) on the level and distribution of heavy elements in the surrounding environment (air, soil and soil biota). Concentrations of As, Cd, Co, Cr, Cu, Hg, Ni, Pb, Sb, Tl and Zn were measured by inductively coupled plasma-mass spectrometry in transplanted lichens, topsoils and isopods. The highest accumulation levels found for Cd, Cr, Pb, Sb and Zn in lichens transplanted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The first phase was to develop a sampling plan and work protocol inspired by previous studies, where samples were collected at variable distances from the stress source (Mazzeo et al 2013 ; Nannoni et al 2015 , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The first phase was to develop a sampling plan and work protocol inspired by previous studies, where samples were collected at variable distances from the stress source (Mazzeo et al 2013 ; Nannoni et al 2015 , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…It can be seen in Table 1 that the average contents of Cr, Cu, Ni, Pb, and Zn (67.77, 23.32, 27.62, 24.71, and 63.07 mg kg -1 , respectively) in soils around the landfill studied (4300 t/d) were significantly higher than those near a landfill in Vientiane, Laos (300 t/d) (Vongdala et al 2019), which might be associated with the greater daily waste disposal capacity of the landfill studied herein. In addition, soil near the landfill studied (8 years in operation) contained lower concentrations of Cr, Cu, and Ni than soils around a municipal solid waste landfill in Pilsen, Czech (21 years in operation; 77.16, 48.41, and 41.47 mg kg -1 , respectively) (Adamcova et al 2016), the Laogang Landfill in Shanghai, China (23 years in operation; 86.00 and 34.00 mg kg -1 for Cr and Ni, respectively) (Liu et al 2013b), and the Ginestreto municipal solid waste landfill in Italy (22 years in operation; 89.00, 25.50, and 54.80 mg kg -1 , respectively ) (Nannoni et al 2017), which might be a result of the shorter time in operation. A previous study (Chang et al 2007) reported that heavy metal pollution tends to be more serious in landfills that have been operating for longer periods of time.…”
Section: Concentrations Of Heavy Metalsmentioning
confidence: 99%
“…Atmospheric deposition is a significant factor affecting the distribution of Hg (Gan et al 2019). Due to its high volatility, Hg easily migrates to topsoil through atmospheric deposition (Nannoni et al 2017;Lv 2019). Thus, factor 4 may be associated with atmospheric deposition of landfill gas.…”
Section: Spatial Distribution Characteristics and Source Identification Of Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the monitoring process, the real-time vehicle location information in the database is read every two minutes to obtain the latest vehicle location information (Nannoni et al, 2017;Siew et al, 2019).…”
Section: Locating the Transportation Location Of Logistics Vehiclementioning
confidence: 99%